The Holocaust and the Canadian War Museum Controversy - Celinscak, Mark (Canadian Jewish Studies / Études juives canadiennes, 2018)
In February 1998 the Senate Subcommittee of Veteran Affairs held hearings to discuss a proposed Holocaust gallery in the Canadian War Museum. The hearings ultimately led to a democratization of the museum’s content and presentation. The controversy also helped lead to the creation of both the Canadian Museum of Human Rights in Winnipeg as well as the establishment of a National Holocaust Monument in Ottawa. Finally, by examining the Holocaust gallery controversy from the perspective of the present day, we can better appreciate a growing body of research that explores how the Canadian government, media, military and average citizen responded to the Holocaust.